2023
DOI: 10.1177/13505076231167265
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to become an-Other critical scholar: Bridging as ‘activist performativity’

Abstract: This essay invites my colleagues in business schools to do their research differently by working with and for community/grassroots organisations. Based on my fieldwork experience at a free food store problematising food surplus and food waste in Aotearoa New Zealand, I offer ‘activist performativity’ as a scholarship modality that builds on critical praxis aligning activism, research and teaching for a socially just and sustainable society. I present my attempt to become an-Other critical scholar bridging mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…for less prestigious outlets that would sustain their critical ethos. Likewise, Alakavuklar's (2017) account showed how, as a non-native English speaker, he negotiated his marginalized subject position by choosing to publish in journals that would lend space to his voice; and, more recently, he described how he is purposefully embracing an activist performativity in his scholarly work (Alakavuklar, 2023). Working from a Global South perspective, Kothiyal et al (2018) suggested that local practices encompassing hybrid doctoral education, indigenous conferences, and linguistic diversity could constitute alternative sites from which to disrupt the dominance of institutional pressures emanating from the Global North.…”
Section: Neoliberalismmentioning
confidence: 99%
See 1 more Smart Citation
“…for less prestigious outlets that would sustain their critical ethos. Likewise, Alakavuklar's (2017) account showed how, as a non-native English speaker, he negotiated his marginalized subject position by choosing to publish in journals that would lend space to his voice; and, more recently, he described how he is purposefully embracing an activist performativity in his scholarly work (Alakavuklar, 2023). Working from a Global South perspective, Kothiyal et al (2018) suggested that local practices encompassing hybrid doctoral education, indigenous conferences, and linguistic diversity could constitute alternative sites from which to disrupt the dominance of institutional pressures emanating from the Global North.…”
Section: Neoliberalismmentioning
confidence: 99%
“…Butler and Spoelstra (2017) illuminated how they undermined the publication “game” by consciously withdrawing from “the excellence regime,”; they purposefully chose to write for less prestigious outlets that would sustain their critical ethos. Likewise, Alakavuklar's (2017) account showed how, as a non-native English speaker, he negotiated his marginalized subject position by choosing to publish in journals that would lend space to his voice; and, more recently, he described how he is purposefully embracing an activist performativity in his scholarly work (Alakavuklar, 2023). Working from a Global South perspective, Kothiyal et al.…”
Section: Literature Reviewmentioning
confidence: 99%